Prognostic Role of FGFR Alterations and FGFR mRNA Expression in Metastatic Urothelial Cancer Undergoing Checkpoint Inhibitor Therapy - Tully, Karl H.; Jütte, Hendrik; Wirtz, Ralph M.; Jarczyk, Jonas; Santiago-Walker, Ademi; Zengerling, Friedemann; Breyer, Johannes; Sikic, Danijel; Kriegmair, Maximilian C.; von Hardenberg, Jost; Wullich, Bernd; Taubert, Helge; et al. (Urology, 2021)
Objective: To examine the disease-specific survival(DSS) after checkpoint inhibitor(CPI) therapy based on FGFR alterations and FGFR mRNA expression levels in patients with metastatic urothelial cancer(mUCa) within a multi-center cohort. Methods: Within a cohort of 72 patients with mUCa from five academic centers in Germany FGFR alterations, as well as FGFR1-4 mRNA expression levels in tumor samples from the primary tumor or metastatic sites. Spearman rank correlations, logistic regression, as well as Kaplan-Meier survival analyses and univariate Cox proportional hazards regression models were employed to examine the impact of different FGFR patterns on the DSS after CPI treatment. Results: FGFR3 mutations or gene fusions (gene alterations) were detected in 16.9% of all samples. Patients with or without FGFR3 gene alterations did not show different oncological outcomes undergoing CPI treatment. Low expression of FGFR2 mRNA alone, as well as the combination of either low FGFR2mRNA expression and FGFR3 gene alteration or high FGFR3mRNA expression (P = 0.027), identified a subgroup of patients with unfavorable outcomes, comprising 40% of the total cohort. This trend was also observed in univariate Cox proportional hazards regression analysis(FGFR3 gene alteration: Hazard ratio(HR) 5.33, 95%Confidence interval(CI)1.76-15.0, P = 0.004; FGFR3mRNA expression:HR 3.04, 95%CI 1.40-7.13, P = 0.005). Conclusion: Assessment of FGFR mRNA expression identified a high-risk subgroup of patients with mUCa. These patients showing overexpression of FGFR3 mRNA were found to have unfavorable DSS after CPI treatment. Using this approach may be suitable for identifying a patient population with poor response to CPI treatment, which may benefit from early FGFR inhibition.
CRIS-Team Scopus Importer:2021-07-30